Earnings management in non-financial firms in Nigeria: Does audit quality matters? - Kayode, Ajape, Mohammed; O, Adelowotan, Michael (Edelweiss Applied Science and Technology, 2025)
The efficacy of the audit function has been questioned due to several instances of financial statement manipulation reported worldwide, which has eroded stakeholders’ confidence in the affairs of listed companies in Nigeria. Audit quality has been identified in the literature as having the potential to reduce earnings management practices. The purpose of this research is to examine the relationship between audit quality and earnings management strategies in publicly traded non-financial companies in Nigeria. An ex-post facto research methodology utilizing a purposive non-probability selection method was implemented to choose a sample of 30 publicly traded companies on the Nigerian Exchange Group (NGX). Data was extracted from the audited financial reports of the selected organizations for a ten-year period (2012-2021). The random effects regression model indicated that the audit quality criteria did not significantly influence the actual earnings management practices of the studied organizations. It is concluded that the Big4-non-Big4 dichotomy, the quantum of audit fees paid, the length of the auditor-client relationship, and the engagement of an industry-specialized auditor would not significantly prevent or reveal the occurrence of real earnings management in the listed non-financial firms in Nigeria. We recommend that firms should downplay the significance of an audit firm's size when engaging its services. Future researchers may consider other parameters and proxies of audit quality. The study extends scholarly discourse on earnings management-audit quality interactions to bolster the understanding of shareholders and other stakeholders regarding the implications of this nexus.